EKSPLORASI PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION BERBASIS KOMPANG PADA MATERI LINGKARAN DI SEKOLAH DASAR - Nurlia Fauzi; Hardi Tambunan; Ruth Mayasari Simanjuntak (STKIP Subang, 2026)
Mathematics learning in elementary schools continues to face challenges in connecting abstract mathematical concepts with students' real-life experiences, particularly in learning circle concepts. This condition often limits students' conceptual understanding because instruction tends to emphasize procedural knowledge rather than meaningful contextual learning. Although Realistic Mathematics Education (RME) has been widely recognized as an approach that promotes contextualized mathematics learning, the integration of local cultural contexts into RME remains limited, especially through the use of kompang, a traditional Malay musical instrument with distinctive circular characteristics. Therefore, this study aims to explore the implementation of Realistic Mathematics Education based on kompang in teaching circle concepts at the elementary school level. A qualitative approach employing a case study design was adopted. Data were collected through classroom observations, semi-structured interviews, documentation, and analysis of instructional materials. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. This study is expected to provide an in-depth understanding of how kompang can serve as a meaningful contextual basis for implementing RME in teaching circle concepts, while offering practical insights into the integration of local cultural resources in elementary mathematics learning.